In situ observations of wintertime low‐altitude clouds over the Southern Ocean ... - Ahn, Eunmi; Huang, Yi; Chubb, Thomas H.; Baumgardner, Darrel; Isaac, Peter; de Hoog, Mark; Siems, Steven T.; Manton, Michael J. (Monash University, 2018)
Cloud droplet concentration (Nd), effective radius (reff) and liquid water content (LWC) measured by a DMT CAPS and an SEA WCM‐2000 of wintertime low‐altitude clouds over the Southern Ocean (SO) are presented for 20 flights taken over 3 years (June–October, 2013–2015). Such clouds have been reported to have the lowest Nd on record (10–40 cm−3) from the Southern Ocean Cloud Experiment (SOCEX I) field campaign in 1993. Of the total 20 357 one‐second records spent in cloud, 38.5% were found to contain ice crystals, primarily in mixed‐phase clouds (36.7%). Ice was observed at some point during 19 of the 20 missions. The droplet spectra and temperature range suggest these clouds were often ideal for the Hallett–Mossop ice multiplication process. The average Nd and reff for liquid clouds were 28 (±30) cm−3 and 12.5 (±2.9) µm, which are consistent with those from SOCEX I. Forty‐nine percent of all liquid cloud samples were observed to be drizzling with an average drizzle rate of 0.733 mm h−1. As drizzle samples ...